On women's films : across worlds and generations - Margulies, Ivone; Szaniawski, Jeremi (New York: Bloomsbury Academic, 2019)
Looks at contemporary and classic films from emerging and established makers such as Maria Augusta Ramos, Xiaolu Guo, Valérie Massadian, Lynne Ramsay, Lucrecia Martel, Rakhshan Bani-Etemad, Chantal Akerman, or Claire Denis. The collection is also tuned to the continued provocation of feminist cinema landmarks such as Chick Strand's Soft Fiction; Barbara Loden's Wanda; Valie Export's Invisible Adversaries, Cecilia Mangini's Essere donne. Attentive to minor moments, to the pauses and the charge and forms bodies adopt through cinema, the contributors suggest the capacity of women's films to embrace, shape and question the world.
Perverse angle: feminist film, queer film, shame / Liza Johnson -- Thinking like a holy girl: a philosophy of Grandma's bedroom / Karen Redrobe -- "Once upon her time?": the cinema of Valérie Massadian, or, living and creating at the periphery of patriarchy / Jeremi Szaniawski. Notes on contributors -- Index of names and titles.
boek
Keywords: Motion pictures and women; Women in motion pictures; Women motion picture producers and directors; Motion pictures and women; Women in motion pictures; Women motion picture producers and directors; Filmregie; Frau; Film